The effect of home ground in the prevalence of toxoplasmosis among group of seropositive Sudanese females, Khartoum - Mosab Nouraldein Mohammed Hamad (جامعة الشيخ عبدالله البدري, 2018)
Abstract: Background: toxoplasmosis is a disease that results from infection with the Toxoplasma gondii parasite, one of the world’s most common parasites1. T. gondii has an environmental stage oocysts are shed in cat feces, sporulate, and disperse in the environment, where intermediate hosts get infected. Oocysts are an important source of infection for both animals and humans. Objective: The purpose of this study was to determine the effect of home ground in the prevalence of toxoplasmosis. Materials and methods: A total of 50 patients diagnosed with toxoplasmosis attending to different hospitals and clinics in Khartoum, Sudan, were enrolled in this study. Results: A total of 50 female patients seropositive with toxoplasmosis attending to different hospitals and clinics in Khartoum, Sudan, were asked to the type of home ground which is covered or not covered their ages ranged between18-48 years, result 48 patients with toxoplasmosis were lived without home ground cover compare to 2 patients lived in homes with covered ground Conclusion: In summary we conclude that the type of home ground was significantly associated increased susceptibility for toxoplasmosis.